POSTURAL STATUS DIFFERENCES IN ELEMENTARY SCHOOL THIRD GRADE PUPILS - Dževad Džibrić; Alija Biberović; Tarik Huremović; Jasmin Bilalić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Disturbed postural status in young school-age pupils is often an indicator of health problems. These problems become more serious if poor posture is not corrected in time. In order to determine differences in postural status of pupils between the initial and final measurements, data were collected on a sample of 90 respondents, of two elementary schools in Tuzla (Mejdan and Jala). The study included 48 girls and 42 boys, 8 ± 6 months years of age. Postural status assessment was conducted by analyzing eight body segments according to Wolanski method. Curriculum of physical and health education was carried out by professors of physical and health education and lasted for one semester. Differences between initial and final measuring were determined by Wilcoxon's test. After the implementation of program the boys achieved progress in 3 and girls in 2 variables out of 8 total variables for postural status assessment.